An introduction to forensic geoscience - Bergslien, Elisa (Chichester, West Sussex : Wiley-Blackwell, 2012)
'Introduces geological fundamentals through medium of forensic science'--
Includes bibliographical references and index.
Keywords: Forensic geology; Environmental forensics